2004
DOI: 10.1093/annonc/mdh465
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of stage I and II Hodgkin's lymphoma with ABVD chemotherapy: results after 7 years of a prospective study

Abstract: The administration of six ABVD cycles is an effective and safe treatment in patients with stage I and II Hodgkin's lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 33 publications
4
18
1
Order By: Relevance
“…A nonrandomized study from Spain demonstrated a PFS rate of 87% and an OS rate of 97% at 78 months in 80 unselected patients with nonbulky stage I and II HL treated in 1990 -2002 with six cycles of ABVD alone, results similar to the MSKCC experience [26]. In a recent retrospective review of 74 patients with nonbulky stage IA, IIA, and IIB HL from the Dana-Farber Cancer Institute treated with chemotherapy only in 1992-2007 (six ABVD, 70 patients; four ABVD, two patients; two ABVD and two etoposide, vinblastine, and doxorubicin, two patients; four ABVD and two doses doxorubicin, two patients), there were no deaths, and the PFS rate at a median follow-up time of 52 months was 90.5% [27].…”
Section: Chemotherapy Alone In the Treatment Of Nonbulky Early-stage Hlsupporting
confidence: 58%
“…A nonrandomized study from Spain demonstrated a PFS rate of 87% and an OS rate of 97% at 78 months in 80 unselected patients with nonbulky stage I and II HL treated in 1990 -2002 with six cycles of ABVD alone, results similar to the MSKCC experience [26]. In a recent retrospective review of 74 patients with nonbulky stage IA, IIA, and IIB HL from the Dana-Farber Cancer Institute treated with chemotherapy only in 1992-2007 (six ABVD, 70 patients; four ABVD, two patients; two ABVD and two etoposide, vinblastine, and doxorubicin, two patients; four ABVD and two doses doxorubicin, two patients), there were no deaths, and the PFS rate at a median follow-up time of 52 months was 90.5% [27].…”
Section: Chemotherapy Alone In the Treatment Of Nonbulky Early-stage Hlsupporting
confidence: 58%
“…The frequency of grade 3 or 4 neutropenia—defined by National Cancer Institute (NCI) common terminology criteria for adverse events (CTCAE) as an absolute neutrophil count (ANC) of <1.0–0.5 × 10 9 /L and <0.5 × 10 9 /L, respectively—in randomized trials involving ABVD chemotherapy ranges from 10 and 66% [13, 19, 20]. The wide range of the occurrence of this problem possibly reflects the varied number of treatment cycles administered in these trials.…”
Section: Abvd and Neutropeniamentioning
confidence: 99%
“…While most ABVD-based clinical trials initiated prior to the introduction of GFs relied on dose alterations as the prime strategy to counter neutropenia, subsequent studies relied on GFs as the preferred way to maintain dose intensity and to prevent neutropenia-related complications [14, 16, 20, 21]. Both granulocyte colony stimulating factor (G-CSF) and granulocyte macrophage colony stimulating factor (GM-CSF) have been used to manage neutropenia in cancer chemotherapy, but neither of them is found to be superior to the other [30].…”
Section: Abvd and Neutropeniamentioning
confidence: 99%
“…In a single-arm phase II trial, Rueda Dominguez et al treated 95 patients with six cycles of ABVD in early-stage HL [37]. Patients were relatively young (median age of 30 years), most had stage II disease (61%), and in total 48% were unfavorable by EORTC criteria.…”
Section: Outcomes After Modifications In Therapymentioning
confidence: 99%